Noccaea birolmutlui, a New Crucifer Species from South West Anatolia, Turkey - Özgi̇şi̇ Kurtuluş; Ocak, Atilla; Özüdoğru, Bariş (Phytotaxa, 2018)
Noccaea birolmutlui Özgişi & Özüdoğru is described as a new species from Kızıldağ National Park, Isparta, in SW Anatolia. It resembles N. ochroleuca but can be readily distinguished by several morphological characters including shape and size of basal/stem leaves, fruit shape, style length, ovule number etc. Nuclear-encoded ribosomal internal transcribed spacer (ITS) region based phylogeny proved that this species clearly differs than N. ochroleuca and these two species belong to different clades in Noccaea s.str. Diagnostic characters, a description, detailed photos and taxonomic comments on the species are given. Morphological affinities and ITS based phylogenetic relationships of new species are discussed. Furthermore, the IUCN Red List category of N. birolmutlui is proposed as critically endangered (CR) due to its limited distribution.